2010
DOI: 10.1038/nature09099
|View full text |Cite
|
Sign up to set email alerts
|

Chemical genetics of Plasmodium falciparum

Abstract: Malaria caused by Plasmodium falciparum is a catastrophic disease worldwide (880,000 deaths yearly). Vaccine development has proved difficult and resistance has emerged for most antimalarials. In order to discover new antimalarial chemotypes, we have employed a phenotypic forward chemical genetic approach to assay 309,474 chemicals. Here we disclose structures and biological activity of the entire library, many of which exhibited potent in vitro activity against drug resistant strains, and detailed profiling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
469
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 528 publications
(487 citation statements)
references
References 27 publications
2
469
1
5
Order By: Relevance
“…New drugs against malaria are urgently needed. Two recent publications describing thousands of compounds active against blood-stage malaria give us hope (22,23). However, elucidation of the compound targets is important for drug development.…”
Section: Discussionmentioning
confidence: 99%
“…New drugs against malaria are urgently needed. Two recent publications describing thousands of compounds active against blood-stage malaria give us hope (22,23). However, elucidation of the compound targets is important for drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of historical GSK data suggested that the main target classes affected by these compounds are malaria kinases, proteases and G-protein coupled receptors (Gamo et al, 2010). In a similar study, a library of nearly 310,000 chemicals, designed to cover a large diversity of bioactive compounds, was screened upon drug sensitive and multidrug resistant P. falciparum strains (Guiguemde et al, 2010). Amongst hits, 172 were cross-validated by three laboratories using distinct assays.…”
Section: Renew Of Phenotypic Screening Approachesmentioning
confidence: 99%
“…9 Where should the search for leads for new antimalarial drugs start? In visionary initiatives, in 2010, St Jude's Children's Research Hospital 10 and Novartis 11 both published the structures of thousands of compounds that inhibit parasite growth, which represents a step change in the number of leads available for drug discovery programs. Also, in 2010, we at GlaxoSmithKline (GSK) published the Tres Cantos Antimalarial Set (TCAMS), 13533 compounds that are the result of screening nearly 2 million compounds from the GSK corporate collection.…”
mentioning
confidence: 99%